The impact of seasonal variations on IVF pregnancy outcomes: a retrospective cohort study in Jinan, China - Hu, Xin; Li, Heng-bing; Song, Jing-yan; Yuan, Hai-ning; Xu, Ying; Ai, Kai-liang; Sun, Zhen-gao; Mu, Zhen-ni (Frontiers in Medicine, 2025)
BackgroundTo evaluate the association between seasonal temperature variations and clinical outcomes of in vitro fertilization (IVF), aiming to provide theoretical foundations for optimizing protocol timing in reproductive medicine.MethodsThis retrospective cohort study analyzed 2,551 first fresh IVF-embryo transfer (IVF-ET) cycles performed at a tertiary reproductive center of The First Affiliated Hospital of Shandong University of Traditional Chinese Medicine between January 2009 and January 2024. The study population comprised normo-ovulatory women aged < 35 years without uterine anomalies or severe male factor infertility (sperm concentration >1 × 106/mL). Cycles were stratified into four seasonal cohorts based on gonadotropin initiation dates: spring (March-May, n = 709), summer (June-August, n = 787), autumn (September-November, n = 640), and winter (December-February, n = 415). Primary outcomes included clinical pregnancy rate (CPR), live birth rate (LBR), miscarriage rate (MR), and Full-Term delivery rate (FTBR), analyzed through multivariable logistic regression models adjusting for mean daily temperature (°C), relative humidity (%), and daylight hours (h).ResultsCompared with the winter control group, risk of miscarriage in cycles initiated in spring showed a statistically significant increase (95% CI 1.019, 2.846; P = 0.042). Although CPR showed no seasonal variation (spring: 54.30%, summer: 52.22%, autumn: 50.47%, winter: 50.36%; P = 0.464), the spring cohort exhibited a numerically higher Full-Term delivery rate (39.07 vs. 34.22%; P = 0.105). Sensitivity analysis using weighted analysis to balance sample sizes across groups revealed significantly higher full-term birth rates in spring compared to winter (P = 0.046) and the live birth rate in spring was also significantly higher than in winter (P = 0.029). For each unit increase in sunlight intensity on the trigger day, the probability of successful pregnancy decreases to approximately 0.978 times the original value (OR = 0.978 per lux-unit increase, 95% CI 0.960–0.997; P = 0.025).ConclusionSeasonal microenvironmental factors during ovarian stimulation may modulate IVF success trajectories, suggesting potential benefits of climate-adaptive protocol personalization in temperate monsoon regions.Clinical trial registrationThis is a retrospective case-control study.